Influence of nanoclay/phenol formaldehyde resin on wood polymer nanocomposites - Rahman, M.R.; Hamdan, S.; Islam, M.S.; Saleh, A.A. (Asian Network for Science Information, 2012)
Selected tropical wood specie was low dense soft wood and it is abundantly available in Borneo Island. This specie is not suitable for construction materials due to their law physical and mechanical properties. In order to overcome this problem the wood species were impregnate by Nanoclay/PF resin system. Raw wood specimens were then placed into an impregnation chamber, in which there was no contact between samples and they were covered completely by nanoclay/PF mixtures. The system was evacuated to 60 mmHg for 30 min. After that, compressed air was applied to the system and maintained at a pressure of 0.52 MPa for 30 min then released. The excess chemicals wiped off the samples. FT-IR spectra indicate the decrease wave number of the peak, ascribed to C-O stretch of C-O-H in starch at 1317 cm-1 and 1222 cm-1 and C-O stretch of C-O-C in starch at 1027 cm-1 confirmed the impregnation of nanoclay/PF wood sample due to the fact that plasticizer could form intense H-bonding interaction with the hydroxyl groups. The MOE and MOR of WPNC were significantly increased compared with raw wood. The Young’s modulus of Eugenia sp. was significantly different between raw wood and WPNC. The XRD patterns of WPNC indicate that the crystallinity increases at the amorphous region due the monomer loading. The SEM micrograph of WPNC clearly shows the void space was filled by the monomer and removes the waxy substance.